DEVELOPMENT OF CULTURAL AND ART INSTITUTIONS - Taslimboyev Azizbek Zokirjon o’g’li; Umidaxon Boltaboyeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Institutions of culture and arts provide quality services to the population, meet their cultural needs and ensure a meaningful leisure time. These institutions include theaters, circuses, philharmonic halls, concert halls, cultural and educational institutions (cultural centers, museums, art galleries), exhibition halls, historical and cultural reserves, parks and gardens, art palaces, educational institutions in the field of culture and arts, etc. This article discusses current issues and solutions for the modern development of cultural and art institutions.